Millennium The end of the world and the forging of Christendom - Holland, Tom
Of all the civilisations existing in the year 1000, that of Western Europe seemed the unlikeliest candidate for future greatness. Compared to the glittering empires of Byzantium or Islam, the splintered kingdoms on the edge of the Atlantic appeared impoverished, fearful and backward. But the anarchy of these years proved to be, not the portents of the end of the world, as many Christians had dreaded, but rather the birthpangs of a radically new order .